Improvement of wheat quality and soil fertility by integrates chemical fertilizer with rhizobial bacteria - Trifa Dhahir Saber; Mohammed Qader Khursheed (Zanco Journal of Pure and Applied Sciences, 2020)
A field experiment was carried out in Erbil city at Agricultural Research Center, during winter season 2017 - 2018, to study the effect of three levels (120, 240, 360 kg.ha-1) of NPK (20:20:20) fertilizer, five species of Rhizobial inoculation (Control, Bradyrhizobium sp. (Vigna) (B1), Rhizobium leguminosarum bv. Viciae (B2). Bradyrhizobium Mungbean (B3), Mesorhizobium ciceri (B4) and Rhizobium leguminosarum bv phaseoli (B5)) and two wheat cultivar soft (Triticum aestivum L.) Hawler2,and hard (Triticum durum L.) Seminto and their combination on leaf (Nitrogen, Phosphor, Potassium, Calcium and Iron)contents, soil nutrient (Total Nitrogen, available Phosphor, Potassium and Iron contents, leaf (Auxin IAA, Gibberellin GA and Cytokinin CK) contents, grain number.plot-1, weight of 1000 grain(g), grain yield kg.hac-1, biological yield kg.hac-1 and harvest index% by utilizing complete randomized block design (CRBD) with three replication. Rhizobial inoculation individually increased significantly all tested parameters of growth. Generally, Seminto significantly surpassed Hawler2 in most traits under study. Interaction between of chemical fertilizer with rhizobial bacteria was more evident than that of chemical fertilizer alone for all mentioned traits. The combination of chemical fertilizer, rhizobial bacteria and wheat cultivars had a synergistic effect and improved leaf (N,P,K,Ca and Fe) contents, fertility of soil, phytohormone concentration in leaves and yield components. The finding indicated that the combination between the lower levels of NPK fertilizer with Rhizobium leguminosarum bv phaseoli inoculation for Triticum aestivum increased grain yield by 114.39% over the control. We recommend using rhizobial bacteria in combination with lower levels of NPK to reduce chemical fertilizer dose and improving yield production and soil fertility because combination between mentioned factors gave the highest values of most traits under study.